2006
DOI: 10.1210/me.2005-0280
|View full text |Cite
|
Sign up to set email alerts
|

The G Protein-Coupled Receptor GPR30 Mediates the Proliferative Effects Induced by 17β-Estradiol and Hydroxytamoxifen in Endometrial Cancer Cells

Abstract: The growth of both normal and transformed epithelial cells of the female reproductive system is stimulated by estrogens, mainly through the activation of estrogen receptor alpha (ERalpha), which is a ligand-regulated transcription factor. The selective ER modulator tamoxifen (TAM) has been widely used as an ER antagonist in breast tumor; however, long-term treatment is associated with an increased risk of endometrial cancer. To provide new insights into the potential mechanisms involved in the agonistic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
249
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(273 citation statements)
references
References 91 publications
20
249
0
4
Order By: Relevance
“…Our previous studies have shown that one micromolar OHT induces cell proliferation in thyroid and endometrial cancer cells by activating the EGFR/GPR30/ERK pathway and in turn c-Fos expression (Vivacqua et al, 2006a(Vivacqua et al, , 2006b, whereas it has no effects on the JNK/ c-Jun pathway (Madeo A, unpublished observations). These observations together with this study lead to the hypothesis that the functional output of c-Fos induction by OHT may depend on whether or not there is a concomitant c-Jun activation by JNK signaling.…”
Section: C-jun Mediates 4-hydroxytamoxifen-induced Apoptosismentioning
confidence: 94%
“…Our previous studies have shown that one micromolar OHT induces cell proliferation in thyroid and endometrial cancer cells by activating the EGFR/GPR30/ERK pathway and in turn c-Fos expression (Vivacqua et al, 2006a(Vivacqua et al, , 2006b, whereas it has no effects on the JNK/ c-Jun pathway (Madeo A, unpublished observations). These observations together with this study lead to the hypothesis that the functional output of c-Fos induction by OHT may depend on whether or not there is a concomitant c-Jun activation by JNK signaling.…”
Section: C-jun Mediates 4-hydroxytamoxifen-induced Apoptosismentioning
confidence: 94%
“…The upregulation of c-fos by estrogen and phytoestrogens has also been shown in breast cancer cells (Maggiolini et al, 2004). Recently, GPR30 has been demonstrated to mediate the proliferative effects of both estrogen and tamoxifen in endometrial cancer cells (Vivacqua et al, 2005) and thyroid cancer cells (Vivacqua et al, 2006). Taken together, these observations suggest that GPR30 may play a role in the regulation of cellular growth, including proliferation and apoptosis.…”
Section: G Protein-coupled Seven Transmembrane Estrogen Receptorsmentioning
confidence: 99%
“…Nevertheless, not all those actions can be attributed to the classical ERs. The ability of E2 to activate G proteins highlighted the role of the orphan G-protein coupled receptor (GPCR) 30 [90, 92, 93], recently renamed GPER (G-Protein coupled Estrogen Receptor).…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Several years later the possible function for GPER was identified by demonstrating protein kinases Erk1 and Erk2 activation induced by E2, as well as by the ER antagonists ICI 182,780 and tamoxifen, in breast cancer cell lines expressing GPER but not in cell lines lacking GPER [89]. Furthermore the up-regulation of c-fos by estrogen and phytoestrogens has also been shown in breast cancer cells [92, 93]. GPER, as the other 906 members of the GPCRs superfamily, is a 7 transmembrane protein (7TM) and its cellular localization is still a matter of debate.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation